2019
DOI: 10.30848/pjb2019-5(13)
|View full text |Cite
|
Sign up to set email alerts
|

Bio-efficacy of Trichoderma isolates and Bacillus subtilis against root rot of muskmelon Cucumis melo L. caused by Phytophthora drechsleri under controlled and field conditions

Abstract: Root rot of muskmelon caused by Phytophthora drechsleri (Tucker) is considered the most important disease limiting muskmelon production in Pakistan. In this study, three molecularly characterized isolates of Trichoderma (T. harzianum HK, T. harzianum HM, T. asperellum TH) and phenotypically characterized isolate of Bacillus subtilis were evaluated against P. drechsleri under laboratory conditions. The different antagonism assays such as, dual culturing, non-volatile, volatile metabolites and field conditions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In particular, PGPR secretes auxins, such as indole-3-acetic acid (IAA), which improve the growth of shoots and roots by increasing root surface area, which in turn, promote nutrient uptake [ 23 , 24 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Specifically, Bacillus species possess significant inhibitory activity against various phytopathogens, including Phytophthora capsici [ 40 , 41 ] and Phytophthora drechsleri [ 42 ]. In addition, Bacillus species are known to produce auxins, which promote plant growth [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, PGPR secretes auxins, such as indole-3-acetic acid (IAA), which improve the growth of shoots and roots by increasing root surface area, which in turn, promote nutrient uptake [ 23 , 24 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Specifically, Bacillus species possess significant inhibitory activity against various phytopathogens, including Phytophthora capsici [ 40 , 41 ] and Phytophthora drechsleri [ 42 ]. In addition, Bacillus species are known to produce auxins, which promote plant growth [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Out of 7 antagonists S-18 (39.6%) isolate showed the highest mycelial growth inhibition against the test fungus as compared to others (Table 3). Similar studies were conducted by (Anjum et al 2019) reported the bioactivity of biocontrol agents against Phytophthora drechsleri infection was studied in vitro. T. asperellum (47.3%) showed the highest growth rate of Phytophthora drechsleri in potato dextrose.…”
Section: In Vitro Screening For Antagonistic Rhizobacteria Against Ph...mentioning
confidence: 53%
“…Moreover, these treatments also presented plant growth-promotion traits, demonstrated by the increase in dry root and dry shoot weights. However, the most efficient treatment was the combination of all biocontrol agents, which showed the minimum percent of disease incidence (20%) and the highest survival rate of plants (80%), as well as the higher dry root and dry shoot weight [46]. Their results suggest that Trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%
“…This subsection will present some works investigating the use of bacteria and fungi tested as biocontrol agents against Phytophthora species. Looking for biological approaches to control the root rot of muskmelon caused by Phytophthora drechsleri (Tucker), Anjum and colleagues (2019) [46] obtained Trichoderma isolates (T. harzianum HM, T. harzianum HK, and T. asperellum TH) and isolated B. subtilis from soil samples collected at the Research Area of the University of Sargodha. All biocontrol agents tested showed mycelial inhibition against P. drechsleri to some degree in dual culture in vitro assays.…”
Section: Studies With Both Fungi and Bacteria As Biocontrol Agents Ag...mentioning
confidence: 99%